Utfodring i finmaskiga hönät : hästens ättid och skötarens arbetsmiljö - Karlsson Budde, Lina; Kjell, Emelie; Ryman, Marie (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2013)

(untitled)
Horses are by nature herbivores, specialized on grass, and graze during the main part of the day. The horse has neither changed this basic behaviour nor the function of gastro-intestinal tract, when the horse was domesticated by man. A horse on pasture has an even production of saliva and gastric acids. The buffering effect of the saliva makes the pH in the stomach above four throughout most of the day. With abnormal long breaks of eating, the pH may decrease, causing an increased risk of gastric ulcer. Due to the physiological and psychological conditions of the horse there are benefits to design a feeding system similar to the natural way of the horse to distribute the time spent on feeding during the day. As the nutritional content in the forage nowadays is fairly high, free access of forage is unsuitable for many horses. A possible way to lengthen the feeding time is to hamper the availability of the roughage using a small-mesh hay-net.